Current approaches in the treatment of septic shock - Ayşe Karabacak; Enver Yazar (Eurasian Journal of Veterinary Sciences)
It is achieved that developments about care-intensive device and drugs, nowadays. However, mortality is still very high in septic shock patients. In this review, it is mentioned that the current approach in the treatment of septic shock.